Soil Fertility Assessment in Sirsa District of Haryana Using Geo-spatial Techniques: Soil fertility assessment using geo-spatial techniques - Verma, Vijendra Kumar; Jakhar, Devender Singh; Raj, Dev; Ranjan, Supriya; Meena, Dileep; Kumar, Sawan; Fagodiya, Ram Kishor; Yadav, Saloni; Patel, Ashish Kumar (Journal of Soil Salinity and Water Quality, 2025)
This study was conducted to evaluate the soil fertility status of Sirsa district of Haryana state, India for sustainable soil management, enhancement of nutrient use efficiency and crop productivity. In 2022, a soil survey carried out which involved the collection of 350 surface soil samples from a depth of 0–15 cm using a systematic sampling method with GPS coordinates. The samples were analyzed for soil pH, electrical conductivity (EC), and the available of nitrogen (N), phosphorus (P), potassium (K), and sulfur (S). The Sulfur Availability Index (SAI) and Soil Nutrient Index (SNI) were calculated based on previously established indices. High-resolution spatial distribution maps of the Sirsa district were prepared to depict the fertility status. The soils were non saline, and slightly to moderately alkaline in nature. Out of total area (4276 km2), entire area was low in available N, about 62% and 51% area were medium in OC and available K, respectively, while about 56% and 58% area were high in available P and S, respectively. Nutrient index values of the district for OC and available K were medium, available N was low and available P and S were high. Sulfur availability index of the district was 8.17. Based on the study, it can be concluded that farmers are encouraged to apply chemical fertilizers based on the soil test results, complemented by bio-fertilizers and organic manures. This integrated nutrient management (INM) approach offers an effective strategy for maintaining soil fertility and promoting sustainable crop production in the region.